Critical thinking in academic writing : a cultural approach - Pu, Shi (London: Routledge, 2022)
"The book compares how critical thinking is conceptualised, applied and acquired by Chinese postgraduate students in three different settings in China and the UK, aiming to uncover the cultural conditions for them to understand and apply critical thinking skills in academic writing tasks. Based on ethnographic fieldwork of eight months, the book analyses students' views of critical thinking, compares their application of critical thinking in their written drafts, and enquires into their accounts of writing experiences. From an insider's perspective, it unpacks the intricate interplay between a range of cultural and individual factors influencing students' critical thinking experiences. By analysing Chinese students' potentials and learning needs, the book offers insights into the nature of problems that they encounter, hoping to open up possibilities for their intellectual growth. The book will primarily be of interest to academics and educators who work with Chinese students. Scholars working on intercultural issues in higher education will also find it helpful"--
Includes bibliographical references and index.
Keywords: Academic writing; Critical thinking; Academic writing -- Cross-cultural studies; Critical thinking -- Cross-cultural studies; Chinese students -- Great Britain; Postgraduate students -- China